A mathematical hysteretic model for elastomeric isolation bearings. - Hwang, J.S.
An analytical model for high damping elastomeric isolation bearings is presented in this paper. The model is used to describe mathematically the damping force and restoring force of the rubber material and bearing. Ten parameters to be identified from cyclic loading tests are included in the model. The sensitivity of the ten parameters in affecting the model is examined. These ten parameters are functions of a number of influence factors on the elastomer such as the rubber compound, Mullins effect, scragging effect, frequency, temperature and axial load. In this study, however, only the Mullins effect, scragging effect, frequency and temperature are investigated. Both material tests and shaking table tests were performed to validate the proposed model. Based on the comparison between the experimental and the analytical results , it is found that the proposed analytical model is capable of predicting the shear force displacement hysteresis very accurately for both rubber material and bearing under cyclic loading reversals. The seismic response time histories of the bearing can also be captured, using the proposed analytical model, with a practically acceptable precision.
Keywords: Seismic isolation; Isolation bearing; Analytical modelling; Shaking table test; Material test